Conversion of hydrogen/carbon dioxide into formic acid and methanol over Cu/CuCr2O4 catalyst. (14th September 2017) - Chiang, Chao-Lung; Lin, Kuen-Song; Chuang, Hui-Wen; Wu, Chun-Ming
Abstract: Cu/CuCr2 O4 catalysts were prepared by impregnation method at various calcination temperatures (300, 400, and 500 °C) and then reduced in H2 stream. The aggregated particles and decreasing surface area/pore volumes of the deactivated catalysts during HCOOH and CH3 OH formations were also observed. Particularly, the EXAFS data showed that first shells of Cu atoms transforms from Cu–O to Cu–Cu after catalytic reactions, their bond distances and coordination numbers are quite different, respectively. It revealed that metallic Cu atoms are one of the important active species over catalyst surface at different reaction temperatures having many unoccupied binding sites for HCOOH and CH3 OH formations. Additionally, the optimal calcination temperature for Cu/CuCr2 O4 catalysts was demonstrated at 400 °C that attributed to its strongest acidity and basicity. The catalytic reactions in the duration of HCOOH and CH3 OH preparation were proposed that were composed of HCOOH formation, CH3 OH formation, and CH3 OH decomposition happening at CuCr2 O4, Cu, and CuO active sites, respectively. The highest CO2 conversion (14.6%), HCOOH selectivity/yield (87.8/12.8%), and TON/TOF values (4.19/0.84) were obtained at 140 °C and 30 bar in 5 h, respectively. Optimal rate constant (2.57 × 10 −2  min −1 ) and activation energy (16.24 kJ mol −1 ) of HCOOH formation were evaluated by pseudo first-order model and Arrhenius equation, respectively. Graphical abstract: Highlights: Cu/CuCr2 O4 with an average diameter of 50 nm was identified by HR-TEM. Cu atoms are the main active species in Cu/CuCr2 O4 by CO2 hydrogenation. CuO can be reduced into Cu in the duration of CO2 hydrogenation at 140 °C. Valuable HCOOH/CH3 OH can be produced by CO2 hydrogenation over Cu/CuCr2 O4 . A mechanism of HCOOH/CH3 OH formation via CO2 hydrogenation was proposed.